2018
DOI: 10.3892/ijmm.2018.3673
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MEK/ERK/STAT3 signaling in oleuropein treatment inhibits myocardial ischemia/reperfusion

Abstract: Studies have shown that oleuropein has antifungal, anti‑inflammatory, antiviral, antioxidant, anticancer and hypoglycemic functions. TTC solution staining was used to measure myocardial infarction size. A commercial kit was used to measure lactate dehydrogenase (LDH), creatinine kinase‑MB (CK‑MB), tumor necrosis factor‑α (TNF‑α), interleukin‑1β (IL‑1β), IL 6, superoxide dismutase (SOD), glutathione (GSH), malondialdehyde (MDA) and catalase levels. Western blot analysis was used to measure p53, p-MEK p-ERK and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 32 publications
(40 reference statements)
1
21
0
Order By: Relevance
“…Recent study suggested protective effect of Ole on myocardial ischemia/reperfusion in neonatal rat cardiomyocytes due to inhibition of apoptosis [201]. Also, Ole inhibited myocardial infarction size and decreased creatinine kinase-MB and LDH serum levels in a myocardial ischemia/reperfusion rat model [202]. Furthermore, it was shown that Ole exerts cardioprotection in cholesterol-fed animals through activation of intracellular signaling, reduces the circulating cholesterol and LDL levels and increases myocardial ATP content [203].…”
Section: Oleuropeinmentioning
confidence: 99%
“…Recent study suggested protective effect of Ole on myocardial ischemia/reperfusion in neonatal rat cardiomyocytes due to inhibition of apoptosis [201]. Also, Ole inhibited myocardial infarction size and decreased creatinine kinase-MB and LDH serum levels in a myocardial ischemia/reperfusion rat model [202]. Furthermore, it was shown that Ole exerts cardioprotection in cholesterol-fed animals through activation of intracellular signaling, reduces the circulating cholesterol and LDL levels and increases myocardial ATP content [203].…”
Section: Oleuropeinmentioning
confidence: 99%
“…Also, GSH critically functions in antioxidant defense and serves as a vital regulator of pathways essential for maintaining body homeostasis [ 43 ]. More importantly, decreased levels of TNF-α, IL-6, and MDA have been observed along with increased SOD and GSH levels have been previously documented following alleviation of MIRI after oleuropein treatment [ 44 ]. Collectively, these findings supported the inhibitory role of miR-206 overexpression in MIRI.…”
Section: Discussionmentioning
confidence: 98%
“…The mechanism of olea derivatives is still unknown. However, recent data showed that, in myocardial I/R rats, OL modulated the ERK pathway and suppressed the induction of p53, p-MEK, and p-ERK protein expression [ 60 ]. Cisplatin-induced acute renal injury was attenuated by OL through the inhibition of p53 and ERK signalling in mice [ 61 ].…”
Section: Candidates For Nutraceutical Supplementation In the Failimentioning
confidence: 99%